An Analysis of the Impact of Social Media on the Communication Ecology of Traditional News Media - Xu, Xinqi (Transactions on Social Science, Education and Humanities Research, 2026)
The rapid rise of social media has dramatically altered the communications environment in which traditional news companies operate, affecting well-established ways of news generation, dissemination and audience participation. This research analyses the multidimensional effects of social media on traditional news media from three theoretical perspectives: media ecology theory, agenda-setting theory and gatekeeping theory. Drawing on empirical data from global audience studies, platform data and new communication literature, the paper discusses how social media has disturbed the attention economy, deteriorated traditional gatekeeping authority and re-aligned intermedia agenda-setting dynamics. It also reflects on the ramifications for news credibility and audience trust and examines the convergence methods with which established media firms are attempting to reconfigure their role in the altered communication environment. Our analysis suggests that while social media has permanently changed the structural conditions of journalism, traditional news media still have unique institutional resources – editorial authority, source credibility and investigative capacity – that make them important nodes in a hybrid information environment.